Օսմանյան կայսրությունում Հայկական հարցի լուծման լիբանանյան մոդելը - Հովհաննիսյան, Նիկոլայ («Զանգակ - 97»)
There were several projects for the Solution of the Armenien question in the Ottoman Empire-implementation o f reforms in the Armenien regions decentralization of the Empire, etc. The paper deals with a model, which was used in the Ottoman Empire for Solution of national question, known as the "Lebanese model". It was first used in 1861, when the Mount Lebanon received some kind of autonomy under the head of а Christian Governos (Mutasarrif), appointed by the Ottoman Sultan by recommendation of European powers, who were the guarantees of the autonomy.
Keywords: Հայոց պատմություն; Հայկական հարց